Identification of IGF2BP3 and CENPA as key regulators of immunophenotypes in renal clear cell carcinoma - Zhu, Tianjie; He, Liying; Li, Shuai; Zhao, Jingyuan (Frontiers in Genetics, 2026)
IntroductionKidney renal clear cell carcinoma (KIRC) is the most common subtype of Renal cell carcinoma (RCC), with a high degree of immune infiltration. This study aimed to identify m6A-related biomarkers and downstream effectors in KIRC that may affect tumor immunity and to provide prognosis biomarkers of KIRC.MethodsIn this study, the mRNA expression profiles and corresponding clinical data of KIRC patients were downloaded from The Cancer Genome Atlas (TCGA) to screen out transcription factors and m6A-related genes that were upregulated and unfavorable to the prognosis of KIRC. The multigene signature was constructed using LASSO analysis to selected two transcription factors and a m6A-associated gene, and TCGA cohort was constructed to stratify patients into two risk groups.ResultsFunctional analysis showed that immune-related pathways were enriched and that immune status was different between the two risk groups, with Insulin-like growth factor 2 mRNA-binding protein 3 (IGF2BP3) and centromere protein A (CENPA) genes highly correlated with immune cell infiltration.DiscussionWe found that silencing CENPA significantly increased reactive oxygen species production and mitochondrial membrane potential abnormalities leading to inhibition of cell viability and proliferation and cell death, suggesting that CENPA is closely associated with the development of KIRC. In conclusion, IGF2BP3 and its downstream CENPA signature can be used for prognostic prediction of KIRC.